Pemodelan Tindak Pidana Kriminalitas di Kota Tangerang Menggunakan Metode Regresi Lasso - Diah Restu Ningsih; Putroue Keumala Intan; Dian Yuliati (Hasanuddin University, 2023)
Criminal acts are one indicator of social welfare for a sense of security. The higher the reporting of criminal cases by the public, it indicates that the level of security in the area is getting worse. Crime acts in Tangerang City can be influenced by several factors, namely the poverty factor, the population factor and the population growth rate factor. If the rate of population growth experiences rapid growth, the population will increase and it is undeniable that poverty will increase in the city of Tangerang. This can trigger criminal acts to meet unsatisfied needs. The purpose of this study is to determine the variables that influence criminal acts in Tangerang City and to overcome the variables that occur multicollinearity. It can be concluded that all variables influence crime and the LASSO (Least Absolute Shrinkage And Selection Operator) regression can simplify the model and indirectly overcome the problem of multicollinearity in this study. So that the government can make more efforts to overcome the population and poverty problems that occur and the police to increase security in the City of Tangerang in order to create even better security and minimize crime.